Ambassador George Buchanan and the July Crisis - Young, John W. (Taylor & Francis, 2018)
During the July Crisis, the United Kingdom was put under strong pressure from Russia and the latter’s ally, France, to declare it would fight alongside them. Britain had made the entente cordiale with France in 1904 and a Convention with Russia in 1907. The British Ambassador to St. Petersburg, George Buchanan, was the key figure in diplomatic communication between Britain and Russia at this time and his performance has drawn diverse comments over the decades. Some analysts believe he genuinely sought to restrain Russia from war, but was undermined by his own government, who too easily accepted St. Petersburg must mobilise its army. But others feel Buchanan’s reports of Russian mobilisation were ill-informed and unhelpful to the government in London. This article examines Buchanan’s performance, arguing that he attempted to preserve peace for a time and does not deserve some of the criticisms levelled at him. Nonetheless, the preservation of the Triple Entente was a priority for him and, after about 28 July, once it became clear that European war could not be avoided, he became tardy in reporting Russia’s war preparations, appearing more interested in defending his hosts’ behaviour than in providing an accurate analysis of events.